Permeability and Dynamic Stability in Porous Asphalt Mixtures Using Cariphalte Asphalt and Gilsonite Additives - Aszharri, Arief; Sari, Nadra Mutiara (Universitas Negeri Padang, 2024)
Porous asphalt mixture is a new generation of flexible pavement that allows water to seep into the top layer (wearing course) both vertically and horizontally. This condition is possible, because the gradation used has a coarse aggregate fraction of not less than 85% of the mixture volume. This layer uses an open gradation (open graded) which is spread over a layer of waterproof asphalt to prevent seepage into the road foundation. This porous asphalt layer can effectively provide a greater level of safety, especially during rainy times to prevent aqua-planing, resulting in rougher surface roughness and can reduce noise (noise reduction). In this research, a test will be carried out on porous asphalt with a mixture using Cariphalte modified asphalt and gilsonite as the added ingredient. Variations in asphalt content used are 4%, 5%, 6%, 7%, 8%. Determination of variations in levels of variation is based on research that has been conducted. This research involves analysis of calculation results based on experimental data from laboratory scale experiments including Marshall Testing, Immersion Index, Permeability, Slip Resistance, Dynamic Stability, and Resilient Modulus. The test results show that the smallest permeability value is in the 8% gilsonite mixture but it does not meet the requirements of AAPA 2004 so the mixture with the greatest stability value is used. From the results of dynamic stability testing, it shows that the mixture of test objects with a content of 7% gilsonite has a dynamic stability value of 5250 passes/mm at a temperature of 45°C and 3150 passes/mm at a temperature of 60°C.